Exploring the phase space of Zn2SbN3, a novel semiconducting nitride. Issue 39 (16th September 2021) - Mis, Allison; Lany, Stephan; Brennecka, Geoff L.; Tamboli, Adele
Abstract : The novel semiconductor Zn2 SbN3 is one of a growing list of ternary nitrides with promise for optoelectronic and energy applications. Abstract : The novel semiconductor Zn2 SbN3 is one of a growing list of ternary nitrides with promise for optoelectronic and energy applications. Previous work by Arca et al. [ Materials Horizons, 2019, 6, 1669–1974] first reported synthesis of this material, but did not explore the effects of growth conditions on material formation. In this work, we present a semi-automated study of the relationship between growth conditions and crystallinity via high-throughput RF sputtering and a custom X-ray diffraction analysis routine. Zn2 SbN3 is found to crystallize in a wide range of growth conditions, and the formation of several contaminant phases is examined. Electron microscopy of these secondary phases, caused both by off-stoichiometry and by growth conditions, provides insight into the growth mechanisms of Zn2 SbN3 . Computational work relates this material to other Zn-based ternary nitrides and offers an explanation for the difficulty of growing cation-ordered material despite the wide range of growth conditions explored.